Hypertension Management in the High Cardiovascular Risk Population - Ilir Maraj; John N. Makaryus; Anthony Ashkar; Samy I. McFarlane; Amgad N. Makaryus (International Journal of Hypertension)
The incidence of hypertension is increasing every year. Blood pressure (BP) control is an important therapeutic goal for the slowing of progression as well as for the prevention of Cardiovascular disease. The management of hypertension in the high cardiovascular risk population remains a real challenge as the population continues to age, the incidence of diabetes increases, and more and more people survive acute myocardial infarction. We will review hypertension management in the high cardiovascular risk population: patients with coronary heart disease (CHD) and heart failure (HF) as well as in diabetic patients.